Clinical recommendations to diagnose and monitor patients with transthyretin amyloid cardiomyopathy in Asia. Issue 9 (6th July 2022) - Lin, Weiqin; Chattranukulchai, Pairoj; Lee, Alex PW; Lin, Yen‐Hung; Yu, Wen‐Chung; Liew, Houng‐Bang; Oomman, Abraham
Abstract: Transthyretin amyloid cardiomyopathy (ATTR‐CM) is a debilitating and life‐threatening condition with a heterogeneous clinical presentation. Recent guidelines from the United States and Europe have been published to guide clinical practice and to facilitate management conformity by covering current diagnostic and treatment strategies for patients with ATTR‐CM. These guidelines highlight the importance of an early diagnosis to optimize therapeutic outcomes, specifying the use of tests and imaging techniques to allow accurate, noninvasive diagnosis of ATTR‐CM. However, as regional practice variations across Asia may limit access to healthcare, availability of specific tests, and expertise in assessing diagnostic images, there is an ongoing need to provide an Asian perspective on these clinical guidelines. This review article provides practical recommendations for the diagnosis and monitoring of patients with ATTR‐CM in Asia, highlighting the need for additional guidelines to support a broad and diverse population, consider differing healthcare systems and diagnostic testing availability, and provide a flexible yet robust algorithm.